Bone marrow transplantation for adolescents and young adults with sickle cell disease: Results of a prospective multicenter pilot study. Issue 4 (11th February 2019) - Krishnamurti, Lakshmanan; Neuberg, Donna S.; Sullivan, Keith M.; Kamani, Naynesh R.; Abraham, Allistair; Campigotto, Federico; Zhang, Wandi; Dahdoul, Thabat; De Castro, Laura; Parikh, Suhag; Bakshi, Nitya; Haight, Ann; et al.
Abstract : We conducted a multicenter pilot investigation of the safety and feasibility of bone marrow transplantation (BMT) in adults with severe sickle cell disease (SCD) (NCT 01565616) using a reduced toxicity preparative regimen of busulfan (13.2 mg/kg), fludarabine (175 mg/m 2 ) and thymoglobulin (6 mg/kg) and cyclosporine or tacrolimus and methotrexate for graft‐vs‐host disease (GVHD) prophylaxis. Twenty‐two patients (median age 22 years; range 17‐36) were enrolled at eight centers. Seventeen patients received marrow from an HLA‐identical sibling donor and five patients received marrow from an 8/8 HLA‐allele matched unrelated donor. Before BMT, patients had stroke, acute chest syndrome, recurrent pain events, were receiving regular red blood cell transfusions, or had an elevated tricuspid regurgitant jet (TRJ) velocity, which fulfilled eligibility criteria. Four patients developed grades II‐III acute GVHD (18%) and six developed chronic GVHD (27%) that was moderate in two and severe in one patient. One patient died of intracranial hemorrhage and one of GVHD. Nineteen patients had stable donor chimerism, 1‐year post‐transplant. One patient who developed secondary graft failure survives disease‐free after a second BMT. The one‐year overall survival and event‐free survival (EFS) are 91% (95% CI 68%‐98%) and 86% (95% CI, 63%‐95%), respectively, and 3‐year EFS is 82%. Statistically significant improvements in the pain interference and physical function domains of health‐related quality of life were observed. The study satisfied the primary endpoint of 1‐year EFS ≥70%. This regimen is being studied in a prospective clinical trial comparing HLA‐matched donor BMT with standard of care in adults with severe SCD (NCT02766465).